2014
DOI: 10.1124/dmd.114.061580
|View full text |Cite
|
Sign up to set email alerts
|

Interspecies Variability in Expression of Hepatobiliary Transporters across Human, Dog, Monkey, and Rat as Determined by Quantitative Proteomics

Abstract: We quantified, by liquid chromatography tandem mass spectrometry, transporter protein expression of BSEP, MATE1, MRP3, MRP4, NTCP, and OCT1 in our human liver bank (n = 55) and determined the relationship between protein expression and sex, age and genotype. These data complement our previous work in the same liver bank where we quantified the protein expression of OATPs, BCRP, MDR1, and MRP2. In addition, we quantified and compared the interspecies differences in expression of the hepatobiliary transporters, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
165
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 161 publications
(177 citation statements)
references
References 29 publications
11
165
1
Order By: Relevance
“…The contribution of both OATPs represents 70% of total hepatic active uptake; the remaining active uptake (30%) is attributed to NTCP (Ho et al, 2006;Kitamura et al, 2008;Bi et al, 2013). Consistent with the contribution of individual transporters to the overall hepatic uptake of RSV, OATPs and NTCP comprise two of the most abundant sinusoidal uptake transporters in human liver tissues, with relative abundance of quantifiable hepatic transporters of 29% and 13%, respectively, when quantified transporter protein expression in a human liver bank (n 5 55) by liquid chromatography-tandem mass spectrometry (LC-MS/MS) (Wang et al, 2015). Furthermore, for most transporters, the expression in the liver tissues was comparable to that in the cryopreserved hepatocytes (Wang et al, 2015).…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…The contribution of both OATPs represents 70% of total hepatic active uptake; the remaining active uptake (30%) is attributed to NTCP (Ho et al, 2006;Kitamura et al, 2008;Bi et al, 2013). Consistent with the contribution of individual transporters to the overall hepatic uptake of RSV, OATPs and NTCP comprise two of the most abundant sinusoidal uptake transporters in human liver tissues, with relative abundance of quantifiable hepatic transporters of 29% and 13%, respectively, when quantified transporter protein expression in a human liver bank (n 5 55) by liquid chromatography-tandem mass spectrometry (LC-MS/MS) (Wang et al, 2015). Furthermore, for most transporters, the expression in the liver tissues was comparable to that in the cryopreserved hepatocytes (Wang et al, 2015).…”
Section: Introductionmentioning
confidence: 80%
“…Consistent with the contribution of individual transporters to the overall hepatic uptake of RSV, OATPs and NTCP comprise two of the most abundant sinusoidal uptake transporters in human liver tissues, with relative abundance of quantifiable hepatic transporters of 29% and 13%, respectively, when quantified transporter protein expression in a human liver bank (n 5 55) by liquid chromatography-tandem mass spectrometry (LC-MS/MS) (Wang et al, 2015). Furthermore, for most transporters, the expression in the liver tissues was comparable to that in the cryopreserved hepatocytes (Wang et al, 2015). In addition to in vitro assessment, RSV has often been used for kinetic studies in vivo in several species, including humans Simonson et al, 2004;Prueksaritanont et al, 2014), monkeys (Shen et al, 2013), mice (Salphati et al, 2014), rats (Wen and Xiong, 2011), and pigs (Bergman et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Cynomolgus monkey cOATP1B1 and cOATP1B3, however, show a high degree of amino acid sequence identity with human orthologs (Shen et al, 2013) but higher hepatic protein amounts as compared with humans (Wang et al, 2015). Both cOATP1B1 and cOATP1B3 are functionally similar to their human orthologs, both in terms of in vitro transport activity and inhibition potency with selected substrates and inhibitors tested (Shen et al, 2013).…”
Section: Introductionmentioning
confidence: 90%
“…For example, hepatic mRNA expression of mouse Oatps gradually increases after birth until adult levels at 6 wk of age (Cheng et al, 2005). In spite of the maturation in animal studies, interspecies differences prevent us from translating animal maturation data to humans (Wang et al, 2015). For humans, only few transporters have been studied, and two recent reviews showed that a clear information gap remains on the developmental trajectory of individual transporters in fetuses and young children and the related impact on drug disposition (Brouwer et al, 2015;Mooij et al, 2015).…”
Section: Introductionmentioning
confidence: 99%